3D printed hydrogel for soft thermo-responsive smart window. (1st June 2022) - Chen, Lei; Duan, Guihui; Zhang, Ce; Cheng, Ping; Wang, Zhaolong
Abstract: Smart windows with tunable optical properties that respond to external environments are being developed to reduce energy consumption in buildings. In the present study, we introduce a new type of 3D printed hydrogel with amazing flexibility and stretchability (as large as 1500%), as well as tunable optical performance controlled by surrounding temperatures. The hydrogel on a PDMS substrate shows transparent-opaque transition with high solar modulation (Δ T sol ) up to 79.332% around its lower critical solution temperature (LCST) while maintaining a high luminous transmittance ( T lum ) of 85.847% at 20 °C. In addition, selective transparent-opaque transition above LCST can be achieved by patterned hydrogels which are precisely fabricated via a projection micro-stereolithography based 3D printing technique. Our hydrogel promises great potential applications for the next generation of soft smart windows.